Pistils - Mapplethorpe, Robert 1946-1989 (Random House, 1996)
Robert Mapplethorpe began taking photographs in the 1970s with a Polaroid camera given to him by a friend. When he died in 1989 of AIDS, at the age of forty-two, he was considered one of the most important photographers of his generation, having gained a reputation as the avatar of a rigorous formalism stunningly wed to graphic and sometimes controversial subject matter. Most of Robert Mapplethorpe's days began in the early afternoon, often by photographing flowers. Mapplethorpe used them to help focus his vision, centering and warming up for his commercial portrait work. The flowers also helped him to effect the transition to the more daring work, which he executed late at night. Pistils reproduces 120 of these ravishing images of flowers, many of which have never been published. The full range of Mapplethorpe's virtuosity is displayed here--early Polaroids: exacting still lifes in black-and-white and color; and extremely rare, toned gravure prints. Not since Georgia O'Keeffe has an artist looked at flowers with as developed an eye as Robert Mapplethorpe. In them he discovered sex, death, redemption, and, always, beauty. These photographs go far beyond decorative allure to place him firmly in the pantheon of the photographic masters.--Publisher's description.
Keywords: Mapplethorpe, Robert; Mapplethorpe, Robert -- 1946-1989; Still-life photography; Photography of plants; Flowers -- Pictorial works; Pflanzenfotografie; Bildband